Stem cell-based photodynamic therapy - Shrestha, Tej Bahadur; Seo, Gwi M.; Basel, Matthew T.; Kalita, Mausam; Wang, Hongwang; Villanueva, David; Pyle, Marla; Troyer, Deryl L.; Bossmann, Stefan H. (My University, 2012)
We have transfected murine neural stem cells (NSCs) and rat umbilical cord matrix-derived stem cells (RUCMSCs) with a plasmid expressing gaussia luciferase (gLuc). These cells are engineered to secrete the luciferase. We have used gLuc containing supernatant from culturing the NSCs to perform in vitro photodynamic therapy of murine melanoma cells (B16F10), and RUCMSCs to perform in vivo PDT of lung melanomas in C57BL/6 mice. The treatment system was comprised of aminolevulic acid as a prodrug for the synthesis of the photosensitizer protoporphyrin IX, gaussia luciferase, and its’ substrate coelenterazine. A significant reduction of the number of live melanoma cells in vitro and a borderline significant retardation of tumour growth in vivo was observed after coelenterazine-mediated PDT.
Keywords: Cancer treatment; Photodynamic therapy; Stem cells